Co-treatment With Everolimus, an mTOR-Specific Antagonist, or Downregulation of ELK1 Enhances the Sensitivity of Pancreatic Cancer Cells to Genistein - Li, Tianyu; Kuang, Tiantao; Yang, Zhaoshuo; Zhang, Qiqi; Zhang, Wen; Fan, Yue (Frontiers in Cell and Developmental Biology, 2021)
Genistein is a natural isoflavone with pharmacological or potentially anti-tumor properties. However, the resistance of cancer cells to genistein remains a major obstacle. This study focused on the mechanism implicated in the resistance of pancreatic cancer (PC) cells to genistein and the mechanism of action. First, key molecules and signaling pathways related to genistein resistance in PC cells were explored using bioinformatics tools. DEPTOR, a typical inhibitor of the mammalian target of rapamycin (mTOR) signaling, was predicted to be poorly expressed in the genistein-resistant PC cells. Thereafter, genistein-resistant PC cells (Panc-1 and PaCa) were constructed. Altered expression of DEPTOR was introduced in cells, and everolimus (ELM), a mTOR-specific antagonist, was administrated in cells as well to examine their roles in genistein resistance. The cell apoptosis was examined in vitro and in vivo in mouse xenograft tumors. The upstream regulator of DEPTOR was predicted via bioinformatic tools. The bioinformatic analyses showed that the PI3K/AKT/mTOR signaling pathway was activated in the setting of DEPTOR downregulation in genistein-resistant PC cells. DEPTOR overexpression reduced the 50% inhibiting concentration (IC50) of genistein in PC cells and suppressed mTOR phosphorylation, and it increased Caspase-3 activity, LDH release and apoptosis in PC cells. ELM treatment enhanced the sensitivity of PC cells to genistein in vitro and it strengthened the tumor-eliminating role of genistein in mice. ELK1, a transcription factor that negatively regulated DEPTOR transcription, was suppressed by genistein. Upregulation of ELK1 suppressed DEPTOR transcription and reduced the genistein sensitivity of cells, and it also blocked the genistein-sensitizing roles of ELM in PC cells. In conclusion, this study demonstrated that ELK1 reduces DEPTOR transcription, leading to mTOR phosphorylation and the drug resistance of PC cells.